Where is research on multicultural educator competence heading? A bibliometric analysis - Qudsiyah, Siti Nurul Hajirotul; Montaño, Elsa Carmen; Rohmadheny, Prima Suci (Journal of Professional Teacher Education, 2024)
In the era of globalization, teachers' multicultural competence is a key factor in creating a learning environment that is inclusive and responsive to cultural diversity. Although research on teachers' multicultural competence has grown rapidly, studies that comprehensively analyze global publication trends in this field are limited. This study aims to identify research trends on teachers' multicultural competence through a bibliometric approach. This study used data from reputable academic databases and analyzed with VOSviewer software to map publication trends, academic collaboration networks, and key emerging themes. The analysis was conducted on 288 articles that met the inclusion criteria, which were selected based on the PRISMA method. The results showed a significant increase in publications related to teachers' multicultural competence since 2020. The United States is the country with the highest contribution of publications, followed by Turkey, China and Canada. Other findings indicate that recent research has focused more on multicultural education implementation strategies, the effectiveness of teacher training, and the relationship between multicultural competence and teaching effectiveness. This research will provide insights for academics, policymakers and education practitioners in designing evidence-based teacher training strategies to improve multicultural competence in educational settings.